THE OCCURRENCE OF INSECTS, FUNGI AND ORGANOLEPTIC CHARACTERISTICS IN STORED COFFEE BEANS IN LAMPUNG - OKKY S. DHARMAPUTRA; SUNJAYA SUNJAYA; INA RETNOWATI; MUHAMMAD AMAD (BIOTROPIA, 1999)
A survey on postharvest handling and technology processing of coffee beans at farmer, trader and exporter levels was conducted in West Lampung and Tanggamus regencies of Lampung province during harvest time (July 1998). Interviews and sampling of coffee beans were carried out during the survey. The number of respondents at farmer, trader and exporter  levels was 22, 20 and 4, respectively, while the number of samples collected from each level was 20. All samples were analyzed for moisture content, physical quality, insect and fungal infestation, reducing sugar content, and coffee cupping. The results of the interviews indicated that postharvest handling and technology processing became better from farmers to exporters. Moisture contents of coffee beans collected from farmers and traders were higher than the tolerable limit recommended by SNI (13%). Physical quality of coffee beans collected from exporters was higher than that collected from farmers and traders. Insects were found on coffee beans collected from farmers, traders and exporters, but the number of species and the percentage of samples infested by insects from each level were relatively low. The predominant species was Liposcelis entomophila. The number of fungal species on coffee beans collected from farmers was higher than  that collected from traders and exporters. The predominant species at the three levels was Aspergillus niger, but the lowest percentage of beans infected by this fungus was found on coffee beans collected from exporters. The lowest percentage of samples infected by all fungi was also found on coffee beans collected from exporters. Reducing sugar content of coffee beans collected from exporters was lower than that from farmers and traders. Aroma and flavor values tended to increase from farmers through traders to exporters, while the body decreased. Some off-flavors (i.e. earthy, mouldy, fermented and woody) were encountered in a few coffee samples from farmers as well as from traders. There was no off-flavor encountered in the coffee samples from exporters. Key words:    Stored products pests/Postharvest handling/Technology processing/Moisture content Physical quality/Insect/Fungi/Reducing sugars/Coffee cupping/Coffee/ Lampung.